Associations of choline intake with hypertension and blood pressure among older adults in cross-sectional 2011–2014 National Health and Nutrition Examination Survey (NHANES) differ by BMI and comorbidity status. Issue 1 (14th July 2022) - Taesuwan, Siraphat; Thammapichai, Paradee; Ganz, Ariel B.; Jirarattanarangsri, Wachira; Khemacheewakul, Julaluk; Leksawasdi, Noppol
Abstract: Blood pressure (BP) is a known cardiovascular risk factor that is hypothesised to be inversely related to choline intake. A previous study suggested that this association may be more apparent in older adults and may differ according to demographic and health characteristics. The primary study objectives are to investigate the cross-sectional associations of total choline intake with BP ( n 843) and prevalent hypertension ( n 2113) among USA adults aged ≥ 65 years using the sample from the 2011 to 2014 National Health and Nutrition Examination Survey. Logistic and multiple linear regression models for complex surveys were employed for hypertension status and BP, respectively. Effect modification by sex, race, BMI and comorbidity status were separately investigated using an interaction term. Choline intake interacted with BMI ( P –interaction = 0·04) such that choline intake tended to be associated with lower odds of hypertension among people with BMI < 18·5 kg/m 2 (OR (95 % CI): 0·64 (0·4, 1·00); P = 0·052). Choline intake was not associated with systolic BP (mean ± sem change per 100 mg of choline: −1·03 ± 0·74 mmHg; P = 0·16). In contrast, its relation to diastolic BP differed by cardiovascular comorbidity ( P –interaction = 0·03) with a non-significant ( P = 0·13) negative direction of association observed among those who were free of comorbidities and a non-significant ( P = 0·26) positive direction observed among those with comorbidities. Collectively, these results suggested that the associations of choline intake with BP levels and hypertension risk among older adults are dependent on other risk factors.